(untitled) (ArtCultura, 2007)
LOPES, Antônio Herculano, VELLOSO, Mônica Pimenta e PESAVENTO, Sandra J. (orgs.). História e linguagens: texto, imagem, oralidade e representações. Rio de Janeiro: Casa de Rui Barbosa/7Letras, 2006, 348 p.